One‐Step Formation of Hybrid Nanocrystal Gels: Deposition of Metal Domains on CdSe/CdS Nanorod and Nanoplatelet Networks. Issue 17 (29th May 2021) - Zámbó, Dániel; Schlosser, Anja; Graf, Rebecca T.; Rusch, Pascal; Kißling, Patrick A.; Feldhoff, Armin; Bigall, Nadja C.
Abstract: Hybrid semiconductor‐based nanocrystals (NCs) are generally synthesized in organic media prior to their assembly into catalytically promising nanostructures via multistep methods. Here, a tunable, easy‐to‐adapt and versatile approach for the preparation of hybrid nanoparticle networks from aqueous nanocrystal solutions is demonstrated. The networks consist of interconnected semiconductor NC backbones (made of CdSe/CdS dot‐in‐rods or core/crown nanoplatelets) decorated with noble metal (Au and Pt) or with metal‐based domains (Co 2+ and Ni 2+ ) demonstrating a powerful synthetic control over a variety of hybrid nanostructures. The deposition of the domains and the formation of the network take place simultaneously (one‐step method) at room temperature in dark conditions without any external trigger. Beside the in‐depth structural characterization of the gel‐like hybrid networks, the wavelength‐dependent optical features are studied to reveal an efficient charge carrier separation in the systems and a controllable extent of fluorescence quenching through the domain sizes. Photoluminescence quantum yields and decay dynamics highlight the importance of fine‐tuning the conduction band/Fermi level offset between the semiconductors and the various deposited metals playing central role in the electron–hole separation processes. This procedure provides a novel platform toward the preparation of photo(electro)catalytically promising hybrid nanostructures (acetogels and xerogels) without the need of presynthetic hybrid particle design. Abstract : A novel one‐step preparation method of porous, hyperbranched semiconductor–metal hybrid gel networks is presented. The formation of the gel structures and the domain deposition simultaneously occur in aqueous solution without external trigger (e.g., light or heat). The in‐depth optical characterization reveals highly efficient charge carrier separation upon illumination, which can be tuned via the Fermi level of the deposited domains.